Managing luxury brands : a complete guide to contemporary luxury brand strategies - Cattaneo, Eleonora (London ; New York, NY : Kogan Page, 2023)
"What are the key components of a luxury brand? How can luxury be marketed successfully in a changing global context? What opportunities does the increasing demand for sustainability and the latest technological developments present?Managing Luxury Brands brings together insights from leading academics in the field to answer these questions and more in this comprehensive guide to luxury brand management. It examines what makes a luxury brand, the changing perception of luxury over time, and how to market luxury brands in light of socio and cultural developments and global market shifts. Featuring discussion points, key concept definitions and further reading suggestions for each chapter, it also explores how brands can embrace end-to-end sustainable luxury and the circular economy, and the opportunities of technological developments such as artificial intelligence, augmented reality and non-fungible tokens (NFTs).Featuring case studies from a range of international brands such as Louis Vuitton, Michael Kors and Shanghai Tang, Managing Luxury Brands combines rigorous academic research with the authors' extensive consulting and industry experience to ensure that complex ideas are firmly grounded in real-world implications and applications throughout. Supported by online resources of lecture slides and video interviews with industry experts, this book is an essential resource for any student studying luxury brand management".
Includes bibliographical references and index.
Keywords: Luxury goods industry -- Management; Tourism